Additive manufacturing in the military and defense industry - Ficzere, Péter (Design of Machines and Structures, 2024)
The use of additive manufacturing technologies is becoming more widespread. Obviously, such a new and innovative technology should also be used in the defence in-dustry, despite the many strict safety criteria that have to be met in this field. The current paper presents, without being complete, some of the notable military applications where additive technologies are expected to become more significant in the near future.